Reformulation of the Law on Financial System Stability Supervision Against the Risk of Digital Crisis and Economic Disruption as an Effort to Strengthen State Capacity Towards Golden Indonesia 2045 - Ridwan Mohamad Faisal; Yopik Gani; Kif Aminanto (Indonesian Journal Publisher, 2026)
The digital economic transformation has changed the structure of the national financial system and given rise to various new forms of risks that have the potential to disrupt national macroeconomic stability, such as cyber attacks on the financial sector, digital bank runs, financial data leaks, digital asset volatility, and the dominance of global technology platforms in payment systems and economic transactions. This study aims to analyze the weaknesses of the legal framework for financial system stability supervision in Indonesia in the face of the risk of a digital crisis, examine the relationship between institutional resilience and state capacity on macroeconomic stability, and formulate a legal reformulation of financial system stability supervision based on digital risks towards Indonesia Emas 2045. This study employs a normative juridical method with legislative and conceptual approaches through an analysis of the Bank Indonesia Law, the Financial Services Authority Law, the Financial System Crisis Prevention and Management Law, the Electronic Information and Transactions Law, and the Personal Data Protection Law. The results of the study indicate that the legal system for financial supervision in Indonesia still faces fragmentation of authority, weak institutional coordination, limited cyber resilience regulations, and the absence of integrated digital financial supervision capable of comprehensively anticipating digital threats. Therefore, legal reform is needed through strengthening cyber financial governance, establishing a digital crisis management framework, integrating a national early warning system, strengthening financial data protection, and developing an adaptive, responsive, and resilient digital financial oversight system to strengthen the state's capacity to maintain macroeconomic stability towards Indonesia Emas 2045.